The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.btre.2020.e00572
|View full text |Cite
|
Sign up to set email alerts
|

Diesel-born organosulfur compounds stimulate community re-structuring in a diesel-biodesulfurizing consortium

Abstract: Highlights A biodesulfurizing consortium consisting of biodesulfurizers and non-biodesulfurizers. Sulfur source-driven compositional shifts in a biodesulfurizing consortium. A biodesulfurizing consortium harbors a non-destructive desulfurization pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Also, the efficiency varies due to the specificity of microorganisms according to the various types of HCS in the crude oil submitted to the biotreatment. Whereas Rhodococcus erythropolis IGTS8 has a tendency of specificity towards DBT more than alkylated forms and BT respectively, Also, each microorganism has special selectivity for which sources of sulfur [ 22 , 32 , 33 ]. Also, the various availability of sources of sulfur compounds generate a competitive in desulfurization, therefore the efficiency with multiple substrates is less than single substrate [ 10 , 26 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the efficiency varies due to the specificity of microorganisms according to the various types of HCS in the crude oil submitted to the biotreatment. Whereas Rhodococcus erythropolis IGTS8 has a tendency of specificity towards DBT more than alkylated forms and BT respectively, Also, each microorganism has special selectivity for which sources of sulfur [ 22 , 32 , 33 ]. Also, the various availability of sources of sulfur compounds generate a competitive in desulfurization, therefore the efficiency with multiple substrates is less than single substrate [ 10 , 26 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a model compounds can be applied to lump and represent the whole fossil fuel especially the recalcitrant HCS [13] such as BT, DBT, DBTO2,M DBTSO2, MgSO4, BNT, DBS, 2,8 DMDBT, 2,6 DNDBT, DMDBT, thianthrene [8,[14][15][16][17][18][19][20][21][22][23]. Finally, the microorganisms of BDS applied on water or coal could be common in application of oil [24].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings showed that NR1 desulfurized DBT via the 4S pathway at a 90% of desulfurization rate. Previously reported strains of the T7b can desulfurize 25–59% DBT, including MG1 consortium and Sphingomonas subarctica ( Awadh et al, 2020 ). Overall, we observed that NR1 is a reflective mangrove bacterium in BDS that can degrade organosulfur compounds found in mangrove ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…IMPS02 is able to remove around 60% of the crude oil's organosulfur from crude oil after incubation at 30 °C for 7 d (Castorena et al 2002). The MG1 consortium and Rhodococcus strain IGTS8 reduced the sulfur content of diesel oil by 25% for 7 d of incubation (Awadh et al 2020).…”
Section: Discussionmentioning
confidence: 99%